PENGELOLAAN KEUANGAN UNTUK MODAL USAHA DAN PEMANFAATAN TEKNOLOGI UNTUK PROMOSI DAN TRANSAKSI QRIS PADA UMKM DI KOTA PALEMBANG - Marlina Widiyanti; Imelda, Taufiq, Zakaria Wahab (JOURNAL OF COMMUNITY DEDICATION, 2023)
Effective financial management and technology utilization have become crucial aspects in developing Micro, Small, and Medium Enterprises (MSMEs). This research aims to examine the practice of financial management as business capital and the implementation of technology, especially the use of QRIS (Quick Response Code Indonesian Standard). The purpose of this community service is to assist MSME players in Palembang City to maximize the use of transaction technology with QRIS to facilitate payment transactions and can immediately practice it. This research uses a descriptive-analytical method by collecting data through interviews and surveys of MSME owners in Palembang City. The results show that most MSMEs in this city face challenges in financial management, especially in financial planning and control. The implementation of QRIS has a positive impact on increasing the visibility of MSMEs in the local market, improving transaction efficiency, and expanding customer reach. In conclusion, good financial management and technology utilization, especially QRIS, have a crucial role in improving the competitiveness of MSMEs in Palembang City.